Conformational dynamics is critical for the allosteric inhibition of cGAS upon acetyl-mimic mutations. Issue 3 (13th January 2021) - Guo, Jingjing; Li, Mengrong; Zhang, Yan; Xi, Lili; Cui, Fengling
Abstract : In the present study, the allosteric inhibition mechanism of cGAS upon acetyl-mimic mutations was investigated, and conformational dynamics was found to be especially critical. Abstract : Detection of cytosolic dsDNA by cyclic GMP–AMP synthase (cGAS) is critical for the immune system to sense and fight against infection, but chronic activation of cGAS by self-DNA leads to autoimmune diseases without effective treatment yet. It was found that acetylation on either Lys384, Lys394, or Lys414 could inhibit the catalytic production of cGAMP by cGAS, and further suppressed self-DNA-induced autoimmunity. However, the implied mechanism remains unclear. Here, extensive molecular dynamics simulations combined with multiple analytical approaches were employed to uncover the allosteric inhibition mechanisms by using the K-to-Q mutations to mimic acetylation. Results suggested that the exterior loops contributed most to the conformational dynamics of cGAS, and two concerted intrinsic motions were observed: the inward/outward or twisting movement for the outer appendage of lobe 1 and the open/closed swing of the active-site loops. Mutations slightly affected the binding of dsDNA and cGAMP. The shift of the conformational sampling of the active-site loops or residues around cGAMP upon mutation might potentially explain the inhibition of cGAS activity. Moreover, the intra- and inter-molecular coupling was weakened upon mutations more or less but via distinct pathways. Hence, conformational dynamics play a vital role in the allosteric inhibition of cGAS upon the studied acetyl-mimic mutations. As the studied acetyl-mimic mutations are located at either the inter-lobe or inter-molecular interfaces, hence except for acetylation, our findings might help the development of new therapeutics against autoimmune diseases due to abnormal cGAS activation by designing inter-lobe or intermolecular allosteric inhibitors.